2021
DOI: 10.3389/fnagi.2021.513605
|View full text |Cite
|
Sign up to set email alerts
|

DHCR24 Knock-Down Induced Tau Hyperphosphorylation at Thr181, Ser199, Thr231, Ser262, Ser396 Epitopes and Inhibition of Autophagy by Overactivation of GSK3β/mTOR Signaling

Abstract: Accumulating evidences supported that knock-down of DHCR24 is linked to the pathological risk factors of AD, suggesting a potential role of DHCR24 in AD pathogenesis. However, the molecular mechanism link between DHCR24 and tauopathy remains unknown. Here, in order to elucidate the relationship between DHCR24 and tauopathy, we will focus on the effect of DHCR24 on the tau hyperphosphorylation at some toxic sites. In present study, we found that DHCR24 knock-down significantly lead to the hyperphosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 61 publications
(139 reference statements)
4
33
0
Order By: Relevance
“…Moreover, in DHCR24 knockout (KO) mice the brain cholesterol lack with age, and brain cholesterol deficiency in 3-week-old was associated with altered membrane composition including disrupted detergent-resistant membrane domain (DRM) structure [ 3 , 71 ]. Similarly, in silencing DHCR24 cell model, it was found that cell desmosterol and 7-dehydrocholesterol (7-DHC) are significantly elevated, and cell cholesterol is greatly decreased [ 9 , 24 , 127 ]. So, this genetic defect manifests that the defect of DHCR24 enzyme activity leads to cholesterol deficiency, suggesting the critical role of DHCR24 in maintaining cholesterol synthesis and homeostasis.…”
Section: The Critical Role Of Dhcr24 In Cholesterol Synthesis and Hom...mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, in DHCR24 knockout (KO) mice the brain cholesterol lack with age, and brain cholesterol deficiency in 3-week-old was associated with altered membrane composition including disrupted detergent-resistant membrane domain (DRM) structure [ 3 , 71 ]. Similarly, in silencing DHCR24 cell model, it was found that cell desmosterol and 7-dehydrocholesterol (7-DHC) are significantly elevated, and cell cholesterol is greatly decreased [ 9 , 24 , 127 ]. So, this genetic defect manifests that the defect of DHCR24 enzyme activity leads to cholesterol deficiency, suggesting the critical role of DHCR24 in maintaining cholesterol synthesis and homeostasis.…”
Section: The Critical Role Of Dhcr24 In Cholesterol Synthesis and Hom...mentioning
confidence: 99%
“…Thus, the above data suggest that downregulation of DHCR24 is obviously linked to the major risk factors from AD, suggesting a potential causative link between DHCR24 downregulation and major risk factors from AD. Moreover, a growing body of research has shown that deficiency of DHCR24 activity could induce lowering cholesterol level of neuronal cells and disruption of membrane lipid-raft structure and function, leading to the disregulation of cellular cholesterol homeostasis, and abnormality of cell signaling [ 3 , 9 , 24 , 71 , 122 ]. In addition, increasing evidences support that downregulation of DHCR24 could lead to Aβ production, apoptosis of neuronal or glial cells, hyperphosphorylation of microtubule-associated protein tau (tau), inhibition of autopagy, and inflammation, which are tightly associated with AD and other degenerative diseases [ 9 , 24 , 45 , 71 , 83 , 95 , 127 , 155 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, knocking out DHCR24 was reported to aggravate Aβ production and accumulation in the AD mouse model ( Crameri et al, 2006 ), and overexpressing DHCR24 could decrease Aβ levels and inhibit Aβ toxicity in vitro ( Sarajärvi et al, 2009 ). Bai et al (2021) indicated that DHCR24 knock-down induced tau protein hyperphosphorylation in SH-SY5Y cells. Another study showed a low serum DHCR24 protein level in AD patients with diabetes mellitus (DM) ( Önmez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%